Hybrids Provide More Options for Fine-Tuning Flowering Time Responses of Winter Barley - Fernández-Calleja, Miriam; Ciudad, Francisco J.; Casas, Ana M.; Igartua, Ernesto (Frontiers in Plant Science, 2022)
Crop adaptation requires matching resource availability to plant development. A tight coordination of plant cycle with prevailing environmental conditions is crucial to maximize yield. It is expected that winters in temperate areas will become warmer, so the vernalization requirements of current cultivars can be desynchronized with the environment’s vernalizing potential. Therefore, current phenological ideotypes may not be optimum for future climatic conditions. Major genes conferring vernalization sensitivity and phenological responses in barley are known, but some allelic combinations remain insufficiently evaluated. Furthermore, there is a lack of knowledge about flowering time in a hybrid context. To honor the promise of increased yield potentials, hybrid barley phenology must be studied, and the knowledge deployed in new cultivars. A set of three male and two female barley lines, as well as their six F1 hybrids, were studied in growth chambers, subjected to three vernalization treatments: complete (8 weeks), moderate (4 weeks), and low (2 weeks). Development was recorded up to flowering, and expression of major genes was assayed at key stages. We observed a gradation in responses to vernalization, mostly additive, concentrated in the phase until the initiation of stem elongation, and proportional to the allele constitution and dosage present in VRN-H1. These responses were further modulated by the presence of PPD-H2. The duration of the late reproductive phase presented more dominance towards earliness, and was affected by the rich variety of alleles at VRN-H3. Our results provide further opportunities for fine-tuning total and phasal growth duration in hybrid barley, beyond what is currently feasible in inbred cultivars.